Unravelling the temporal dynamics of community functions in protists induced by treated wastewater exposure using metatranscriptomics - Manan Shah; Guido Sieber; Aman Deep; Daniela Beisser; Jens Boenigk (Scientific Reports)
Abstract The discharge of treated wastewater (TWW) into freshwater ecosystems poses a significant impact on microbial communities, particularly protists, which play a crucial role in nutrient cycling and ecosystem stability. While the ecological effects of TWW on microbial diversity have been studied, understanding the functional responses of protist communities remains limited. This study employs metatranscriptomics to unravel the temporal dynamics of protist community functions in response to TWW exposure. Using mesocosm experiment, water samples were analyzed over a ten-day period to monitor shifts in metabolic pathways and community interactions. Our results indicate that processed metatranscriptomic data, focusing on treatment-significant pathways, is more sensitive than traditional methods, such as meta-barcoding, and non-target screening, in detecting wastewater-induced perturbations. Early exposure to TWW significantly altered expression of pathways associated with signal transduction and environmental interaction, while general metabolic pathways showed resilience. Over time, the protist community showed signs of adaptation with expression levels stabilizing towards the end of the experiment. This study underscores the importance of focussing on functional shifts rather than just taxonomic changes for assessing wastewater impacts on freshwater ecosystems. Our findings advocate for the use of metatranscriptomics as a robust indicator for TWW detection, aiding in development of targeted environmental management strategies.